Experimental and Modelling Studies of CO2 Adsorption by Activated Carbon Derived from Rubber Seed Shell - Ramdan, Amira Nurain (Universiti Teknologi PETRONAS, 2016)
The aim of this research is to study the feasibility of using rubber seed shell as potential adsorbent for eliminating carbon dioxide from polluted air in the atmosphere. This project work highlights on the constraints involved in the preparation of the activated carbon derived from rubber seed shell, such as activating agent, impregnation ratio, activation temperature and time of activation. Initially, the dried rubber seed shell is grinded into 0.25mm size, then chemically activated using potassium hydroxide (KOH) and carbonized at altered ranges of temperature and duration. The activated carbons produced are characterized by using Tristar 3020, Scanning Electron Microscope (SEM) and HPVA II analyzer. Sample R273 was identified to yield activated carbon with largest surface area, SBET of 1129.68 m2 /g and pore diameter, 3.46 nm which falls in mesoporous category.